2019
DOI: 10.1016/j.bbamcr.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Dual-specificity MAP kinase phosphatases in health and disease

Abstract: It is well established that a family of dual-specificity MAP kinase phosphatases (MKPs) play key roles in the regulated dephosphorylation and inactivation of MAP kinase isoforms in mammalian cells and tissues. MKPs provide a mechanism of spatiotemporal feedback control of these key signalling pathways, but can also mediate crosstalk between distinct MAP kinase cascades and facilitate interactions between MAP kinase pathways and other key signalling modules. As our knowledge of the regulation, substrate specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 199 publications
(371 reference statements)
1
85
0
Order By: Relevance
“…DUSP5 is a nuclear protein, and it dephosphorylates the threonine/tyrosine residues of ERK1/2 to affect numerous cellular functions, which contributes to the pathogenesis in many diseases (Lake, Correa, & Muller, ; Mandl, Slack, & Keyse, ; Seternes, Kidger, & Keyse, ; Zhang et al, ). We previously reported that the myogenic response and autoregulation of cerebral and renal blood flow (CBF and RBF) are enhanced in Dusp5 KO rats (Fan et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…DUSP5 is a nuclear protein, and it dephosphorylates the threonine/tyrosine residues of ERK1/2 to affect numerous cellular functions, which contributes to the pathogenesis in many diseases (Lake, Correa, & Muller, ; Mandl, Slack, & Keyse, ; Seternes, Kidger, & Keyse, ; Zhang et al, ). We previously reported that the myogenic response and autoregulation of cerebral and renal blood flow (CBF and RBF) are enhanced in Dusp5 KO rats (Fan et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…MKPs are classified into three subgroups: tyrosine-specific phosphatases, serine-threonine phosphatases or dual-specificity (threonine/tyrosine) phosphatases (DS-MKPs), which represent the best-characterized class [ 13 ]. Currently, at least ten main DS-MKPs have been identified [ 14 ]. Based on their subcellular localization, DS-MKPs are divided into type I, II and III.…”
Section: The Mapk Familymentioning
confidence: 99%
“…In this study, we found that MAPK pathways, particularly ERK1/2, were activated by FGF‐2 via FGFR‐1 and were associated with eotaxin‐1 production in ASCs. Proteins in the MAPK family mediate many cellular functions, including protein expression, proliferation, and apoptosis (Puddicombe and Davies, 2000; Seternes et al, 2019). ERK1/2, JNK, p38 MAPK, ERK3/4, and ERK5 play central roles in these cell responses.…”
Section: Discussionmentioning
confidence: 99%